PROMIS Physical Function Computer Adaptive Test Compared With Other Upper Extremity Outcome Measures in the Evaluation of Proximal Humerus Fractures in Patients Older Than 60 Years. Issue 6 (June 2015) - Morgan, Jordan H.; Kallen, Michael A.; Okike, Kanu; Lee, Olivia C.; Vrahas, Mark S.
Abstract : Objectives: To compare the PROMIS Physical Function Computer Adaptive Test (PROMIS PF CAT) to commonly used traditional PF measures for the evaluation of patients with proximal humerus fractures. Design: Prospective. Setting: Two Level I trauma centers. Patients/Participants: Forty-seven patients older than 60 years with displaced proximal humerus fractures treated between 2006 and 2009. Intervention: Evaluation included completion of the PROMIS PF CAT, the Constant Shoulder Score, the Disabilities of the Arm, Shoulder, and Hand (DASH) and the Short Musculoskeletal Functional Assessment (SMFA). Main Outcome Measurement: Observed correlations among the administered PF outcome measures. Results: On average, patients responded to 86 outcome-related items for this study: 4 for the PROMIS PF CAT (range: 4–8 items), 6 for the Constant Shoulder Score, 30 for the DASH, and 46 for the SMFA. Time to complete the PROMIS PF CAT (median completion time = 98 seconds) was significantly less than that for the DASH (median completion time = 336 seconds, P < 0.001) and for the SMFA (median completion time = 482 seconds, P < 0.001). PROMIS PF CAT scores correlated statistically significantly and were of moderate-to-high magnitude with all other PF outcome measure scores administered. Conclusions: This study suggests using the PROMIS PF CAT as a sole PF outcome measure can yield an assessment of upper extremity function similar to those provided by traditional PF measures, while substantially reducing patient assessment time.